2011
DOI: 10.1614/wt-d-10-00013.1
|View full text |Cite
|
Sign up to set email alerts
|

Light-Activated, Sensor-Controlled Sprayer Provides Effective Postemergence Control of Broadleaf Weeds in Fallow

Abstract: A study was conducted in summer fallow fields near Davenport, WA, and Pendleton, OR, in 2007 and 2008 to evaluate the POST weed control efficacy of herbicide treatments applied with a light-activated, sensor-controlled (LASC) sprayer compared to the broadcast application of glyphosate. The LASC application of glyphosate alone (at all rates) and in mixture with pyrasulfotole plus bromoxynil or 2,4-D had weed control (≥ 88%) and dry weight (≤ 6% of control) similar to the broadcast application of glyphosate acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Light-activated sensor-controlled (LASC) or Weed Seeker ® sprayers have shown tremendous success in site-specific weed control and in reducing herbicide costs by 30% to 70% in fallow (Ahrens 1994; Biller 1998; Blackshaw et al 1998; Jha et al 2014; Riar et al 2011). In addition, the LASC sprayer has shown 25% reductions in herbicide cost for selective weed control in cereals and pea compared with a broadcast application (Dammer and Wartenberg 2007).…”
Section: Management Of Hr Bassia Scopariamentioning
confidence: 99%
“…Light-activated sensor-controlled (LASC) or Weed Seeker ® sprayers have shown tremendous success in site-specific weed control and in reducing herbicide costs by 30% to 70% in fallow (Ahrens 1994; Biller 1998; Blackshaw et al 1998; Jha et al 2014; Riar et al 2011). In addition, the LASC sprayer has shown 25% reductions in herbicide cost for selective weed control in cereals and pea compared with a broadcast application (Dammer and Wartenberg 2007).…”
Section: Management Of Hr Bassia Scopariamentioning
confidence: 99%
“…The site-specific control of spraying was based either on infestation maps prepared offline or on real-time optical sensing systems, including machine vision, able to detect weed patches on bare soil or within row crops (Miller 2003). These systems have evolved through further research (Gerhards et al 2002;Nordmeyer 2006;Christensen et al 2009;Riar et al 2011;Berge et al 2012) which overall reported a wide range (from 5% to almost 90%) of potential savings in herbicide, depending mainly on the spatial and temporal distribution of weeds found in the treated plots.…”
Section: Literature Review On Precision Spraying Equipmentmentioning
confidence: 99%
“…It is just as important to rotate herbicides as it is to rotate crops to reduce overall loading rates of any one herbicide. In addition, reduction in herbicide application rates are now enabled by the advent of imaging-based precision herbicide technologies capable of targeting post-emergence weeds in fallow (Riar et al, 2011).…”
Section: Crop Diversificationmentioning
confidence: 99%